Maternal autoimmune diseases and the risk of tics and Tourette's disorder in offspring: insights from Taiwan's real-world data - Lee, Yi-Feng; Wu, Meng-Che; Huang, Yen-Chu; Huang, Jing-Yang; Wei, James Cheng-Chung (Frontiers in Pediatrics, 2025)
BackgroundCurrently, tics and Tourette's disorder are burdensome neurological disorders that manifest in vocal and motor tics with onset during childhood. Previous studies have demonstrated that maternal autoimmune diseases may cause several neurodevelopmental disorders in offspring via maternal immune activation. However, the association between them has never been thoroughly researched. Thus, in this study, we aimed to explore whether maternal autoimmune diseases are associated with the risk of tics and Tourette's disorder in offspring in a real-world nationwide population-based cohort study.MethodsWe analyzed offspring with or without autoimmune disease exposure between 2009 and 2016 from national population databases in Taiwan. Multivariate analysis, multiple Cox regression analyses, and stratified analyses were conducted in the study.ResultsIn total, 76,411 offspring with autoimmune disease exposure and 1,211,936 offspring without maternal autoimmune disease exposure were selected and analyzed in this study. The incidence of childhood tics and Tourette's disorder was 2.35 [95% confidence interval (CI) 2.23–4.86] and 1.89 (95% CI 1.86–1.92) per 10,000 person-months in children exposed to maternal autoimmune disease and non-exposed children, respectively. The children whose mothers had an autoimmune disease had a 1.26-fold risk of tics and Tourette's disorder compared to children whose mothers did not have an autoimmune disease [crude hazard ratio: 1.26; 95% CI, 1.20–1.34, adjusted hazard ratio (aHR): 1.22; 95% CI, 1.15–1.29]. Offspring of mothers with rheumatoid arthritis (aHR: 1.46, 95% CI, 1.07–1.97), system lupus erythematosus (aHR: 1.57, 95% CI, 1.18–2.09), Sjogren's syndrome (aHR: 1.28, 95% CI, 1.09–1.50), ankylosing spondylitis (aHR: 1.49, 95% CI, 1.07–2.09), Graves’ disease (aHR: 1.26, 95% CI, 1.15–1.37), Hashimoto's thyroiditis (aHR: 1.59, 95% CI, 1.29–1.98), and type I diabetes (aHR: 1.68, 95% CI, 1.13–2.50) had a significantly higher risk of developing tics and Tourette's disorder. Aside from maternal autoimmune diseases, mothers with urinary tract infections, diabetes mellitus, hyperlipidemia, anemia, a sleep disorder, endometriosis, and depression were also associated with childhood tics and Tourette's disorder.ConclusionMaternal autoimmune diseases appeared to be associated with tics and Tourette's disorder in offspring, especially in mothers with the abovementioned diseases. Further research is warranted to investigate the possible pathogenetic mechanisms of these associations.